The 12 worst human-made disasters of all time - Hamen, Susan E. (All-time worst disasters., 2019)
Profiles history's twelve worst man-made disasters, documenting their location, lives lost, and legacy. Each profile includes images and statistics, and select entries include critical thinking questions. Includes tips on how to stay safe during a hurricane, a glossary, sources for further information, and an index.